ISM-based evaluation of Air Pollution Control Measures - Anjali and Prof. Madan Lal (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
Addressing Air Pollution is crucial as it profoundly affects environmental sustainability, public well-being, and economic stability. As the world deals with the growing consequences of greenhouse gases, understanding their significance is crucial for devising effective solutions and fostering a global commitment to environmental stewardship. This paper outlines the critical importance of addressing pollution by mapping air pollution mitigation strategies. This study explores practical strategies for mitigating air pollution by conducting a comprehensive literature review followed by Interpretive Structural Modelling (ISM), used to analyse and understand the intricate interconnections between different mitigation strategies. In conclusion, air pollution is a significant global challenge that requires collaborative efforts, innovative solutions, and effective policies. Therefore, there is a dire need to reduce emissions, enhance air quality, and protect health and well-being globally.